FACTORS CAUSING VIOLATIONS OF THE TRADITION OF ABANDONMENT IN THE COMMUNITY OF SINGKARAK AND SANIANG BAKA NAGARI, SOLOK REGENCY - Yosrizal Yosrizal; Maria Montessori; Fatmariza Fatmariza; Junaidi Inderawadi (Indonesian Journal of Social Science Education (IJSSE), 2026)
This study examines the factors causing violations of the tradition of abstinence-based marriage among the Singkarak and Saniang Baka communities in Solok Regency, West Sumatra. This prohibition is rooted in Minangkabau customary law, which is based on historical narratives about kinship relationships and social agreements among traditional leaders. Despite its long-standing existence, violations of this tradition have increased in practice. This study uses a descriptive qualitative approach with literature review, sociological analysis, and simulated field data that reflect empirical reality. The results indicate that violations are influenced by modernization, increased formal education, reinterpretation of religious teachings, weakening customary authority, increased individual autonomy, and high social mobility. These findings indicate a shift from collective adherence to customary norms to individual decision-making. This research contributes to the study of customary law transformation in contemporary Minangkabau society.